Pencarian Lokasi Tempat Ibadah Terdekat di Kota Bengkulu Menggunakan Algoritma Ant Colony Optimization (ACO) - Agung Kharisma Hidayah; Nur’aini Nur’aini; Anisya Sonita; Saparudin Saroni (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
As a country with a population that has various religions, including Islam, Christianity, Buddhism and Hinduism, Indonesia also has many places of worship spread throughout the region. Bengkulu is an area visited by many tourists, both local and foreign. Therefore, public facilities in Bengkulu are very necessary, one of the facilities needed is a place of worship. Information about places of worship is important and needed by tourists, especially information about the nearest route that can be taken to the place of worship. This research was carried out in order to build a system that can provide information on the nearest places of worship as well as directions that can be used as a guide to that location by implementing the Ant Colony Optimization Algorithm to find the nearest route. This application, which was created using the PHP programming language and MySQL database, can be used with various devices because this application is website-based. The application of the Ant Colony Optimization algorithm produces a route that has the shortest distance to the location of the place of worship.